Detecting the Delayed Signatures of Changing Sediment Supply in Salt-Marsh Landscapes: The Case of the Venice Lagoon (Italy) - Roner, Marcella; Ghinassi, Massimiliano; Finotello, Alvise; Bertini, Adele; Combourieu-Nebout, Nathalie; Donnici, Sandra; Gilli, Adrian; Vannacci, Martina; Vigliotti, Luigi; Bellucci, Luca G.; Fedi, Mariaelena; Liccioli, Lucia; et al. (Frontiers in Marine Science, 2021)
Many salt-marsh systems worldwide are currently threatened by drowning and lateral erosion that are not counteracted by sufficient sediment supply. Here we analyze the response of a salt-marsh system to changes in sediment availability and show that, contrary to what would have been expected, marsh dynamics in the vertical plane can be insensitive to large sediment supply. We integrate sedimentological, geochronological, paleoecological, geophysical, and chemical analyses of salt-marsh sediments accumulated over the past six centuries in the Southern Venice Lagoon (Italy), to provide evidence for the existence of a time lag between the increase in river-fed clastic sediment input and its signature in the salt-marsh succession. This time lag is caused by the stocking of the sediment along the margins of pre-existing marshes, which started to significantly expand horizontally - rather than accrete vertically - when sediment input increased. When sediment input was drastically decreased, wind waves re-suspended the river-fed deposits and distributed them over the marsh platform, eventually allowing for vertical accretion. Understanding the response of salt-marsh systems to changes in sediment supply has important implications for the management of tidal landscapes and the prediction of their evolution under the effects of natural and anthropogenic forcings. Our results highlight that the study of ultra-recent sedimentary successions needs to be carried out on the basis of a deep understanding of specific depositional dynamics.